Characteristic of Nata de Seaweed with Different Concetrations of Bacteria Acetobacter xylinum - Nur Avia Rachmawati; Sakinah Haryati; Aris Munandar (JURNAL PERIKANAN DAN KELAUTAN, 2017)
Nata is a food which is obtained from the fermentation by the bacteria A. xylinum which has a chewy, transparent and soft texture. Seaweed can be used as a media in making nata because the content of carbon source for bacterial growth. The purpose of this research was to determine the concentration of optimum bacteria in producing the best nata de seaweed. The research was conducted on September-October 2016 at the Laboratory of Fishery Products Processing Technology, Department of Fisheries, Faculty of Agriculture, University of Sultan Ageng Tirtayasa and Laboratory of Seafast Center Quality and Food Safety, Bogor Agricultural University. The treatment was about the difference of A. xylinum bacteria concentration (5%, 7.5%, 10%, 12.5% and 15%). The parameters were physical analysis (rendemen and thickness), chemical(hard fiber content and water content) and organoleptic test (appearance, flavor, colour,aromaand texture). This research used Completely Randomized Design (CRD) with two replication.the result of research showed that nata de seaweed with the best treatment 5% produced has an average yield values betwen 16.15g/L, thickness 0.41 cm, content of crude 5.86%, content of water 99.21%, appearance 3.83%, flavor 3.17%, colour 4.13%, aroma 3.13%, texture 3.67%. It can be concluded that the treatment of bacterial concentration with 5% was the best treatment in producing an appropriate characteristic of nata de seaweed.